2(4-3n)=-5n

Simple and best practice solution for 2(4-3n)=-5n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4-3n)=-5n equation:



2(4-3n)=-5n
We move all terms to the left:
2(4-3n)-(-5n)=0
We add all the numbers together, and all the variables
2(-3n+4)-(-5n)=0
We multiply parentheses
-6n-(-5n)+8=0
We get rid of parentheses
-6n+5n+8=0
We add all the numbers together, and all the variables
-1n+8=0
We move all terms containing n to the left, all other terms to the right
-n=-8
n=-8/-1
n=+8

See similar equations:

| 8−n=5 | | 1+2m-+2=3+m | | f−2/2=2 | | (w+8)=w | | p−3/2=2 | | -3x-2=7(2x+7) | | 24=4x+8,x= | | 5x+2+5x-8=74 | | 24=4x+8x= | | x+2=10,x= | | 4-p=1 | | 6x+10=-4(x-5) | | 4x+5+5x-7=79 | | 3x-5-2x=-4 | | r+15=4r−6 | | 14+2p=-6(1-2p) | | x+5=3/4 | | 3(p−4)=9 | | 4/3x=-2/3 | | 4x+6=8x-8 | | 28=0.57x | | 11^-9x=15^-x-5 | | 173=89-v | | 8q^2-3q=7q^2-5q+48 | | u-0.75=2.6 | | 2x+2(x12)=56 | | X+12(x+12)=56 | | y-9.95=1.59 | | -15-8=-7n-6n | | 7(-2k-3)=9 | | 3(-8v+4)=-3(7v-8) | | 5-8(a+7)=-115 |

Equations solver categories